Method to assess lateral handling qualities of aircraft with wingtip morphing - Dussart, Gaétan X.; Yusuf, Sezsy Y.; Portapas, Vilius; Lopez Matos, Guillermo E.; Lone, Mohammad M. (Cranfield University, 2018)
The impact of in- ight folding wingtip on roll characteristics of aircraft has been studied in the past. In this study, a handling qualities assessment carried out to de-risk further development of such a device. A specialised ight simulation campaign is prepared to evaluate the roll dynamics in di erent morphing con gurations. Various manoeuvres, including the O set Landing Manoeuvre and herein presented Slalom and Alignment Tracking task are used. Cooper Harper Rating scales and ight data analysis are used to collect pilot opinion and validate pilot-in-the-loop simulation results. This example is used to demonstrate the use of the slalom and Alignment Tracking manoeuvre for lateral dynamic assessment.